Evaluating Dialogic Engagement of a Mining Company via Communication in Facebook - Mahfud Sholihin, Mahfud Sholihin (2015)
Purpose - The purpose of this study is to attempts to evaluate the extent of dialogic engagement that exist in mining companies Facebook fan page disclosures.